Penerapan Model Pembelajaran Partisipatif Dalam Pendidikan Kesetaraan Di Pusat Kegiatan Belajar Masyarakat (PKBM) Melati Kelurahan Juppandang Kecamatan Enrekang - Muhammad Iqbal; Suparman; Uli Nuha; Elihami; M. Hatta (Mataram University, 2026)
This study aims to analyze the implementation of participatory learning models in equality education at PKBM Melati, Enrekang Regency. The study focuses on the learning process, the roles of tutors and learners, and the factors influencing its implementation. A qualitative descriptive approach was employed, with data collected through interviews, observations, and documentation. The findings reveal that participatory learning has been partially implemented, particularly in the learning process through discussions, experience sharing, and contextual problem-solving activities. However, learner involvement in planning and evaluation stages remains limited, indicating that the participatory cycle has not been fully applied. Tutors have begun to act as facilitators, although their role is still partially dominant. Learners show increased engagement, but participation levels vary due to differences in confidence and learning readiness. Supporting factors include learner motivation, positive social interaction, and flexible learning environments, while inhibiting factors involve limited tutor competence, time constraints, and inadequate learning facilities. The study concludes that participatory learning has the potential to enhance engagement and empowerment, but requires more comprehensive implementation and institutional support to achieve optimal outcomes in nonformal education.